Motive of crossing the Water in the Russian Wedding of Udmurtia - S. V. Tolkachova (Tsentr nauchnykh i obrazovatelnykh proektov, 2019)
The article is devoted to the implementation peculiarities of the motive of crossing the water in the Russian wedding rituals of the modern Udmurt Republic. The relevance of the work is due to the fact that the motive of crossing over water was first considered in the context of wedding folklore found in the territory of the modern republic. The results of the analysis of a number of wedding customs are presented in which the motive of crossing the water is symbolically represented in the action code of the wedding ritual. It was revealed that in these wedding episodes the water was endowed with a “fateful” role. Particular attention is paid to the consideration of texts of wedding songs. The associative links of water as a magical cleansing element and its properties such as changeability, fluidity, with the "transitional" status of the bride in a wedding ceremony are shown. As a result of the analysis of the texts of wedding songs, it was found that the implementation of the motive of the crossing in the Russian wedding folklore of the Udmurt Republic involves several imaginative spheres - a sphere associated with the mythological water and hydronyms; images of transport; a sphere uniting the image of a bridge and buildings, objects and actions similar to it. It is shown that new representations of the crossing can be added to the characteristic manifestations of its motive: the crossing without the participation of water space; textual description and identical kinetic interpretation of a bridge crossing in the action code.